(untitled) (Global Journal of Human-Social Science, 2021)
The State and the Business Activity have a relationship of Interdependence That holds the punitive and regulatory power this the economic The achievement of the global Sustainability goal implies harmony between the actors for joint policies In view of this it aims to demonstrate the participation of the business sector to achieve this objective through socio-environmental management - with the organization or business financially viable fair to the Company and endowed with environmental responsibility To do so the relationship between the human being and the environment is first analyzed in order to identify the consequences of human performance over time Subsequently the application of Sustainability as a concept to the application of management policies for the business sector is studied considering the awareness developed about the existence of a Risk Society as well as the possibility of benefits arising from this management model The method used was inductive